2023
DOI: 10.1098/rspb.2022.2203
|View full text |Cite
|
Sign up to set email alerts
|

Landscape-scale forest cover drives the predictability of forest regeneration across the Neotropics

Abstract: Abandonment of agricultural lands promotes the global expansion of secondary forests, which are critical for preserving biodiversity and ecosystem functions and services. Such roles largely depend, however, on two essential successional attributes, trajectory and recovery rate, which are expected to depend on landscape-scale forest cover in nonlinear ways. Using a multi-scale approach and a large vegetation dataset (843 plots, 3511 tree species) from 22 secondary forest chronosequences distributed across the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…This demonstrates a rapid shift of species compositions after abandonment and a slowing down of community changes in the later stages. Furthermore, the high variation in the early stages of recovery in our study systems might be affected by variation in forest cover in the surrounding as recently shown as relevant for predictability of forest regeneration 48 . Second, additional anthropogenic impacts as logging or hunting 20 , 49 can strongly affect the local fauna, but are not represented by recovery age.…”
Section: Resultsmentioning
confidence: 80%
“…This demonstrates a rapid shift of species compositions after abandonment and a slowing down of community changes in the later stages. Furthermore, the high variation in the early stages of recovery in our study systems might be affected by variation in forest cover in the surrounding as recently shown as relevant for predictability of forest regeneration 48 . Second, additional anthropogenic impacts as logging or hunting 20 , 49 can strongly affect the local fauna, but are not represented by recovery age.…”
Section: Resultsmentioning
confidence: 80%
“…To assess the most appropriate management strategies for natural regeneration, we need to identify the composition and con guration of landscapes that enable or obstruct frugivore seed dispersal into open areas [33][34][35][36]. Recent evidence highlights the correlation between landscape forest cover and forest regeneration [37]. However, the mechanisms underpinning this pattern haven't been explored.…”
Section: Discussionmentioning
confidence: 99%
“…We then calculated the Akaike information criterion corrected for small samples (AIC c ) of all models (null, linear, and nonlinear) across all 13 scales. Following several studies of the scale of effect (e.g., Arroyo‐Rodríguez, Rito, et al, 2023; Jackson & Fahrig, 2015), we identified the model with the highest empirical support (i.e., with the lowest AIC c ; Burnham & Anderson, 2002) as the best model. We then compared the best linear model, the best nonlinear model, and the null model considering their relative empirical support (ΔAIC c ).…”
Section: Methodsmentioning
confidence: 99%
“…The smallest scale was selected so that it included all subsamples in each landscape, and the largest one to avoid landscape overlapping, which can decrease both the variability of the explanatory variable and the independence among landscapes (Eigenbrood et al, 2011;Pasher et al, 2013). We also did not consider larger scales because there is evidence that the number of tropical trees in human-modified landscapes is strongly related to forest cover in 1-km-radius landscapes (Arroyo-Rodríguez, Rito, et al, 2023), and we found no evidence that there existed stronger forest loss effects at larger scales (see the scales of effect of forest cover in Table 1).…”
Section: Landscape Forest Covermentioning
confidence: 99%